Quantifying the effects of achilles tendon lengthening surgery: An intraoperative approach - Brendecke, Elena; Tsitlakidis, Stefanos; Götze, Marco; Hagmann, Sébastien; Ates, Filiz (Frontiers in Physiology, 2023)
Achilles tendon lengthening (ATL) is frequently used in the treatment of foot deformities. However, there is currently no objective method to determine the optimal muscle length during surgery. We developed an intraoperative approach to evaluate the passive and active forces of the triceps surae muscle group before and after ATL and aimed to test the following hypotheses: (i) the ankle passive range of motion (ROM) increases, (ii) passive muscle forces decrease post-ATL, and (iii) forces measured from patients with non-neurological and neurological conditions demonstrate different characteristics. Passive forces at various ankle joint positions were measured in ten patients (11.3 ± 3.0 years old) pre- and post-ATL using a force transducer attached to the Achilles tendon. In six patients, active isometric forces were measured by stimulating the triceps surae supramaximally. Passive forces decreased by 94.3% (p<0.0001), and ROM increased by 89.4% (p<0.0001) post-ATL. The pre-ATL passive forces were 70.8 ± 15.1% lower in patients with idiopathic foot deformities than in patients with neurological conditions (p<0.001). The peak active force of 209.8 ± 114.3 N was achieved at an ankle angle of 38.3° ± 16.0°, where the passive force was 6.3 ± 6.7 N. The inter-individual variability was substantial in both groups. In conclusion, the hypotheses posed were supported. The present findings suggest that muscle passive and active force production as well as the inter-individual variability should be considered when planning further treatment. Clinical Significance: This intraoperative approach providing immediate data would assist in determining the optimal muscle-tendon length and improve the objective outcomes.